النشر العلمي المصري على المستوى الدولي بقواعد بيانات تحليل الاستشهادات المرجعية - حسين، أحمد عبدالحميد (جامعة القاهرة - كلية الآداب - قسم المكتبات والوثائق وتقنية المعلومات, 2022)
يعد النشر الدولي العلمي في أية جامعة من الجامعات أهم مقومات وجودها كمؤسسة تعليم عال. لذا تأتي أهمية هذه الدراسة من أهمية النشر الدولي العلمي لإيصال المعرفة الرصينة للإنتاجية العلمية لأعضاء هيئة التدريس بالجامعات المصرية للالتحاق ونشر أبحاثهم في قواعد بيانات الاستشهادات المرجعية مثل: قاعدتي بيانات Web of Science وقاعدة بيانات Scopus. وذلك في ظل الصعوبات المتعلقة بالنشر الدولي العلمي وانخفاض مؤشراته في الجامعات المصرية، والذي يعد بمثابة المرآة الحقيقية لأي مؤسسة علمية تطمح إلى إخراج قيمة علمية يستفاد من خلالها المجتمع، لذلك هدفت الدراسة إلى رصد مجريات النشر العلمي الدولي، وبيان مؤشراته بالجامعات المصرية، والكشف عن التواجد الدولي للدوريات المصرية، وكذلك استكشاف الإنتاجية العلمية لأعضاء هيئة التدريس بالجامعات المصرية في قواعد البيانات العالمية. وقد اعتمدت الدراسة على المنهجين: المنهج الببليومتري، والوصفي التحليلي لتحليل الإنتاج الفكري الذي تم تجميعه والخروج بمؤشرات متعلقة بحركة النشر العلمي المصري على المستوى الدولي بقواعد بيانات الاستشهادات المرجعية، وقد توصلت الدراسة إلى العديد من الصعوبات التي تقف عائقا أمام النشر الدولي بالجامعات المصرية، والتي يعد من أهمها: عدم دراية الكثير من الباحثين بالمعايير الخاصة بالنشر الدولي في قواعد البيانات العالمية، وقد أوصت الدراسة بضرورة رفع الوعي لدى أعضاء هيئة التدريس والباحثين بالجامعات المختلفة بأهمية النشر الدولي كمعيار رئيسي في التصنيفات العالمية للجامعات، إضافة إلى ضرورة الالتزام بالمعايير التي تضعها إدارة قواعد البيانات العالمية لاختيار وتغطية الدوريات العلمية بها، مع ضرورة النظر في سياسات تحرير الدوريات المصرية وتحديثها مع الأسس والمعايير العالمية.
International scientific publishing in any of the universities is the most important component of its existence as a higher education institution, and one of the main objectives in the movement of authorship and scientific research in universities, as well as one of the elements supporting and strongly to raise the university’s ranking in international classifications. Therefore, the study deals with the Egyptian scientific publishing movement at the international level by rules Reference citation data, so the importance of this study stems from the importance of international scientific publishing for the delivery of solid knowledge of scientific productivity for faculty members in Egyptian universities to join and publish their research in reference citation databases such as the Web of Science database and the Scopus database. This is in light of the difficulties related to international scientific publishing and its low indicators in Egyptian universities, which is the true mirror of any scientific institution aspiring to produce a scientific value from which society can benefit. The refore, the study aimed at monitoring the course of international scientific publishing, showing its indicators in Egyptian universities, revealing the international presence of Egyptian periodicals, as well as exploring the scientific productivity of faculty members in Egyptian universities in global databases. The study relied on the two approaches, the bibliometric approach, as well as the descriptive and analytical method for analyzing the intellectual production that was compiled and coming up with indicators related to the publication of the Egyptian scientific publishing movement at the international level with reference databases. The study concluded that there are many difficulties that stand in the way of international publication in universities The study recommended the necessity of raising awareness among faculty members and researchers in different universities of the importance of international publishing as a main criterion in the international rankings of universities, in addition to the necessity of adhering to the standards set by them, the most important of which is the lack of knowledge of many researchers. Managing global databases for selecting and covering scientific periodicals in them, with the need to consider the policies of editing Egyptian periodicals and updating them with international principles and standards.
Keywords: المكتبات والمعلومات -- قواعد البيانات -- الاستشهادات المرجعية -- النشر العلمي -- مصر